Simple protocol to extract DNA from bone fragments-A preliminary study - Siriwadee Chomdej (Faculty of Veterinary Medicine, Chiang Mai University, 2020)
Chiang Mai Veterinary Journal” (ISSN-print as 1685-9502 and ISSN-online as 2465-4604) before officially changing over to an electronic platform. The newly formatted journal is entitled “Veterinary Integrative Sciences” (ISSN as 2629-9968).